Spontaneous Coronary Artery Dissection Across the Health Care Pathway: A National, Multicenter, Patient‐Informed Investigation - Bouchard, Karen; Lalande, Kathleen; Coutinho, Thais; Mulvagh, Sharon; Pacheco, Christine; Liu, Shuangbo; Saw, Jacqueline; So, Derek; Reed, Jennifer L.; Chiarelli, Alexandra; Stragapede, Elisa; Robert, Helen; et al. (Journal of the American Heart Association, 2023)
Clinical practice guidelines for the management and convalescence of patients with spontaneous coronary artery dissection (SCAD) have yet to be developed. The targeted content, delivery, and outcomes of interventions that benefit this population remain unclear. Patient-informed data are required to substantiate observational research and provide evidence to inform and standardize clinical activities. Patients diagnosed with SCAD (N=89; 86.5% women; mean age, 53.2 years) were purposively selected from 5 large tertiary care hospitals. Patients completed sociodemographic and medical questionnaires and participated in an interview using a patient-piloted semistructured interview guide. Interviews were transcribed and subjected to framework analysis using inductive and then deductive coding techniques. Approximately 1500 standard transcribed pages of interview data were collected. Emotional distress was the most commonly cited precipitating factor (56%), with an emphasis on anxiety symptoms. The awareness and detection of SCAD as a cardiac event was low among patients (35%) and perceived to be moderate among health care providers (55%). Health care providers' communication of the prognosis and self-management of SCAD were perceived to be poor (79%). Postevent psychological disorders among patients were evident (30%), and 73% feared recurrence. Short- and longer-term follow-up that was tailored to patients' needs was desired (72%). Secondary prevention programming was recommended, but there were low completion rates of conventional cardiac rehabilitation (48%), and current programming was deemed inadequate. This early-stage, pretrial research has important implications for the acute and long-term management of patients with SCAD. Additional work is required to validate the hypotheses generated from this patient-oriented research.